Comparison of the zooplankton abundance and diversity in Bolusao and Poblacion Rivers of Lawaan, Eastern Samar - Abria, Eugene G.
Lawaan, Eastern Samar has two major river systems, the Bolusao and the Poblacion Rivers. These two rivers were studied for its zooplankton diversity and abundance from October 2017 to November 2017 and January 2018 to February 2018. Thus, this study aims to assess and compare the zooplankton abundance and diversity in relation to the physicochemical parameters and the abundance of phytoplankton in the Bolusao and the Poblacion Rivers. Sample collection was conducted once a month from the upstream, midstream and downstream portions of the two rivers using a 20 micrometer mesh conical plankton net by a vertical drag technique. Diversity, similarity and correlation analysis was computed using the Shannon-Weiner Diversity Index, Jaccard's Similarity Index and Pearson's Product Moment Correlation Coefficient in the two rivers from the data gathered. The two rivers' zooplankton diversity was composed of 6 phyla, 14 classes, 13 orders and 21 families with both rivers' downstreams having the most families observed. Bolusao and Poblacion Rivers have high diversity values with peaks of 6.4045 and 6.3679, respectively. Poblacion and Bolusao have peaks of 1067 ind/L and 602 ind/L for cell density, respectively. The most abundant of the zooplankton group are the copepods. The two rivers only had 9% similarity. There was a positive correlation between the zooplankton abundance and phytoplankton abundance and physicochemical parameters.